TO THE 90TH ANNIVERSARY OF BIRTHDAY OF PROFESSOR V.G. BELIKOV - B. V. Borovsky; M. V. Larsky; O. O. Frolova (Volgograd State Medical University, Pyatigorsk Medical and Pharmaceutical Institute, 2015)
The article is devoted to basic life milestones of Professor, Doctor of Pharmaceutical Science, Honored Scientist of Russia V.G. Belikov, who made a great contribution to the development of domestic pharmaceutical education and science, more than 30 years headed the leading pharmaceutical institution of the country.